(untitled) (Global Journal of Management and Business Research, 2022)
Who would have thought that after 30 years since the UN Convention on Climate Change the gap between the agreed goals and delivery on them remains so wide and that consequently global warming continues unabated Except for the decrease in CO2 emissions in 2020 resulting from the economic crisis of the time emissions remain essentially the sameas those prevailing before the pandemic reflecting stagnant levels for more than 20 years With lackluster economic performance skyrocketing energy prices and turbulent supply chains it shouldn t be surprising that we may have another year of stagnant CO2 emissions which may revert as soon as economic activity recovers